Labrum and rotator cuff injuries in the throwing athlete - Menge, T. J.; Byram, I. R.; Boykin, R. E.; Bushnell, B. D. (The Physician and Sportsmedicine, 2015)
The large amount of force imparted across the shoulder during the act of throwing makes the glenohumeral joint highly susceptible to injury in the athlete performing overhead throwing motions. The bony incongruity of the shoulder enables greater range of motion than any other joint in the body, but it also results in significant strain on the surrounding soft tissues during the throwing motion. Throwers can present with acute injuries, but more commonly they suffer from chronic overuse conditions resulting from repetitive overload. Proper management requires early recognition with treatment directed toward the athlete`s safe return to sports. Failure to institute an appropriate management strategy may result in significant complications, including prolonged disability, progression of symptoms, and further injury. We discuss the functional anatomy, pathophysiology, clinical presentation, evaluation, and treatment of common injuries of the glenoid labrum and rotator cuff in the overhead throwing athlete.